“Xorijiy tillarni o‘qitishning zamonaviy tendensiyalari masalalari: Hajviy she’rlarda hayot haqiqati. - Soatova, nodira (FILOLOGIYA UFQLARI JURNALI, 2024)
This article is dedicated to the study of comic poems and parablesfrom the lyrics of Shuhrat (Ghulam Aminov), a prominent poet of the 20th century. The article analyzes the poet’s comic poems such as "The Fox and the Hare", "The Frog" and "There was a wolf, it was a fox", "The pale fly". As a result, the author’s fables and comic poems, by boldly reflecting the social-political, spiritual-ethical issues of the time in his poems, clearly show the weaknesses, defects, flaws, and wrong actions of human nature. It was revealed that he revealed it through sharp humor.